Intronic variant screening with targeted next-generation sequencing reveals first pseudoexon in LDLR in familial hypercholesterolemia. (March 2021) - Reeskamp, Laurens F.; Balvers, Manon; Peter, Jorge; van de Kerkhof, Laura; Klaaijsen, Lisette N.; Motazacker, Mahdi M.; Grefhorst, Aldo; van Riel, Natal A.W.; Hovingh, G. Kees; Defesche, Joep C.; Zuurbier, Linda
Abstract: Background and aims: Familial hypercholesterolemia (FH) is caused by pathogenic variants in LDLR, APOB, or PCSK9 genes (designated FH+). However, a significant number of clinical FH patients do not carry these variants (designated FH-). Here, we investigated whether variants in intronic regions of LDLR attribute to FH by affecting pre-mRNA splicing. Methods: LDLR introns are partly covered in routine sequencing of clinical FH patients using next-generation sequencing. Deep intronic variants, >20 bp from intron-exon boundary, were considered of interest once (a) present in FH- patients (n = 909) with LDL-C >7 mmol/L (severe FH-) or after in silico analysis in patients with LDL-C >5 mmol/L (moderate FH-) and b) absent in FH + patients (control group). cDNA analysis and co-segregation analysis were performed to assess pathogenicity of the identified variants. Results: Three unique variants were present in the severe FH- group. One of these was the previously described likely pathogenic variant c.2140+103G>T. Three additional variants were selected based on in silico analyses in the moderate FH- group. One of these variants, c.2141-218G>A, was found to result in a pseudo-exon inclusion, producing a premature stop codon. This variant co-segregated with the hypercholesterolemic phenotype. Conclusions: Through a screening approach, we identified a deep intronic variant causal for FH. This finding indicates that filtering intronic variants in FH- patients for the absence in FH + patients might enrich for true FH-causing variants and suggests that intronic regions of LDLR need to be considered for sequencing in FH- patients. Graphical abstract: Image 1 Highlights: Intronic variants in low-density lipoprotein receptor gene ( LDLR ) can cause familial hypercholesterolemia (FH) but are often neglected. A novel approach to detect these FH-causing variants revealed c.2141-218G > A in LDLR . This variant causes the first ever described occurrence of a pseudo-exon in LDLR . c.2141-218G > A is the deepest known FH-causing variant to date. This emphasizes the need to consider whole LDLR gene analysis in FH.